Ocular Coherence Tomography Unveils Alport Syndrome: A Critical Tool in Detecting Collagen IV Nephropathies - Abdelrahman Ibrahim; Zena Altawallbeh; Monica Patricia Revelo; Martin Gregory; Laith Al-Rabadi (Case Reports in Nephrology)
Collagen IV pathogenic variants are present in Alport syndrome (AS) and some forms of familial focal segmental glomerulosclerosis (FSGS). These conditions pose diagnostic challenges due to overlapping clinical, histological, and genetic features. Ocular coherence tomography (OCT) has emerged as a pivotal diagnostic tool by revealing ocular manifestations characteristic of AS. Here, we present two cases initially diagnosed with primary FSGS but later found to harbor collagen IV pathogenic variants. Both cases progressed to end-stage kidney disease (ESKD) needing transplantation. OCT revealed severe temporal macular thinning consistent with AS in both cases. Our findings highlight the critical role of OCT in distinguishing the subtle differences in the presentation of collagen IV nephropathies. OCT proves valuable for clinicians, particularly when COL4 nephropathies present ambiguous or overlapping features. In such instances, OCT serves to establish precise diagnoses, preventing unnecessary immune suppression. Therefore, incorporating OCT alongside genetic and histological evaluations is crucial for accurate diagnosis, management, and appropriate genetic counseling. Furthermore, recognizing the prevalence of AS accurately is pivotal for conducting population-based studies, which are essential for advancing our understanding of the condition, improving patient care, and informing future research initiatives.